Re-Tubularization of Highly-Ischemic Anti-Mesenteric Border (Rehab): A Novel Bowel Preservation Technique in Complex Gastroschisis - Richard J Hendrickson; Ashwini S Poola; Katherine W Gonzalez; Joel D Lim; Tololupe A Oyetunji (EL-Med-Pub, 2017)
Complex gastroschisis with bowel necrosis poses an operative challenge. Surgeons must weigh the decision between resection versus preservation of ischemic bowel. As one of the leading causes of short bowel syndrome, aggressive resection in complicated gastroschisis subjects children to prolonged dependence on parenteral nutrition and its attendant complications. Herein, we describe a novel technique aimed towards bowel preservation in complex gastroschisis patients with severe bowel ischemia with the ultimate goal for enteral autonomy.